2016
DOI: 10.1093/ijnp/pyw078
|View full text |Cite
|
Sign up to set email alerts
|

N-3 Polyunsaturated Fatty Acids through the Lifespan: Implication for Psychopathology

Abstract: Objective:The impact of lifetime dietary habits and their role in physical, mental, and social well-being has been the focus of considerable recent research. Omega-3 polyunsaturated fatty acids as a dietary constituent have been under the spotlight for decades. Omega-3 polyunsaturated fatty acids constitute key regulating factors of neurotransmission, neurogenesis, and neuroinflammation and are thereby fundamental for development, functioning, and aging of the CNS. Of note is the fact that these processes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 190 publications
1
33
0
Order By: Relevance
“…DHA is not only an important polyunsaturated fatty acid in the central nervous system, but it is also the main constituent of n-3 polyunsaturated fatty acids in cell membranes of cortical gray matter neurons (16). There is limited research on the impact of supplementation with PUFAs on TBI (17)(18)(19). Nevertheless, these studies (17)(18)(19) have consistently demonstrated the protective effects of PUFAs against behavioral deficits and cellular degeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHA is not only an important polyunsaturated fatty acid in the central nervous system, but it is also the main constituent of n-3 polyunsaturated fatty acids in cell membranes of cortical gray matter neurons (16). There is limited research on the impact of supplementation with PUFAs on TBI (17)(18)(19). Nevertheless, these studies (17)(18)(19) have consistently demonstrated the protective effects of PUFAs against behavioral deficits and cellular degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited research on the impact of supplementation with PUFAs on TBI (17)(18)(19). Nevertheless, these studies (17)(18)(19) have consistently demonstrated the protective effects of PUFAs against behavioral deficits and cellular degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Because v-3 and v-6 long-chain polyunsaturated fatty acids (LCPUFAs) are critical for cognitive (12)(13)(14)(15)(16)(17)(18)(19) and metabolic development (20)(21)(22)(23)(24)(25)(26)(27), we focus here on a-linolenic acid (ALA, C18:3 v-3) and linoleic acid (LA, C18:2 v-6), which are obtained solely from dietary sources and are mostly converted in the liver to docosahexaenoic acid (DHA, C22:6 v-3) and arachidonic acid (AA, C20:4 v-6) (28), respectively. Many studies have focused either on overall restriction (29)(30)(31) or supplementation (32,33) with dietary v-3 LCPUFA; however, the ratio between dietary LA and ALA is a key determinant of v-3 LCPUFA status because LA and ALA compete for conversion to their respective LCPUFAs by the same enzymes.…”
mentioning
confidence: 99%
“…According to a meta-analysis of the biological status of n-3 PUFAs in mood disorder, plasma and brain EPA and DHA levels were found reduced in in patients with depression [81]. Interestingly, despite the inverse association between dietary fish consumption and depression incidence, and the positive association between increase of eicosanoids production, depression and SCZ [82], the causal relationship between n-3 PUFAs supplementation, Firmicutes to Bacteroidetes ratio and antidepressant effects is still poorly understood. As observed for depression, plasma EPA and DHA levels are found decreased in ASD children [83,84].…”
Section: Dietary Lipids: Fatty Acids Alteration Of Microbiota Diversmentioning
confidence: 99%